A process study of the Adriatic‐Ionian System baroclinic dynamics. Issue 8 (16th August 2016) - Reale, M.; Crise, A.; Farneti, R.; Mosetti, R.
Abstract: The driving mechanisms behind the decadal reversal of the Ionian Sea upper layer circulation recently sparked a considerable discussion in the Mediterranean scientific community. It has been suggested that the reversal can be driven by variations in wind stress curl over the basin, baroclinic dynamics acting within the Adriatic‐Ionian System (AISys) or baroclinic dynamics driven by thermohaline properties at the AISys eastern boundary. Here we perform numerical simulations in order to assess the relative importance of remote forcings (wind stress, thermohaline fluxes, thermohaline open boundary conditions) on the vorticity and energy budget of the Ionian Sea. A mechanistic understanding of the AISys dynamics is achieved with an approach based on an increasing complexity in the model forcings and domain. Our experiments suggest that wind stress does not play a leading role in the vorticity and energy budgets of the Ionian Sea. Wind stress can reinforce or weaken the circulation but it is not able to reverse its sign. Its role becomes dominant only in the absence of inflows through the Antikythira Strait and Cretan Passage. Instead, reversals in the upper layer circulation of the Ionian Sea take place only in the presence of an active boundary on the Aegean Sea/Levantine Basin side and appear to be correlated with substantial exchanges of Availalble Potential Energy between the two basins (as observed at the end of the Eastern Mediterranean Transient). From an energetic point of view, AISys can be explained therefore only if the role of the Aegean Sea is explicitly considered. Key Points: Wind does not play a leading role in the vorticity and energy budgets of the Adriatic‐Ionian System Reversals in the Ionian Sea take place only in the presence of an active boundary on the Aegean Sea/Levantine Basin side Reversals appear to be correlated with substantial exchanges of Availalble Potential Energy between Ionian and Aegean Sea